Dealing with Difficult Days: Can Experiential Avoidance and Functional Dimensions of Coping Explain Change in Self-harm Thoughts and Behaviour? - Nielsen, Emma Louise (2021)
Self-harm affords people a means of coping, at least in the short term. The reasons most consistently given for self-harm pertain to the reduction of intense aversive emotions; relief from a terrible state of mind. A contemporary theoretical account of non-suicidal self-injury, the Experiential Avoidance Model (EAM: Chapman et al., 2006), proposes that experiential avoidance – the tendency for non acceptance or avoidance (e.g., escape; suppression; modification; control) of negative affective, but not overtly dangerous, states – may be a central psychological factor in the development of, and cyclical reengagement in, self-injurious behaviours. While the EAM framework is specified for non-suicidal behaviours, notions of avoidance and escape motives, related to psychological distress, are also established in models of suicidal behaviours.